"I Just Did Everything Physically Possible to Get in There": How Men and Women Chemists Enact Masculinity Differently. (December 2015) - Hirshfield, Laura E.
This ethnographic study focuses on how men and women chemistry graduate students are socialized to "do masculinity" differently in scientific contexts. Using results from nine months of observation and 40 semistructured interviews from five labs at a research-intensive university, I argue that the link between men, science, and academia may allow men, but not women, graduate students leeway in establishing their claim to scientific authority. Thus, men graduate students may be able to perform gender in more varied and complex ways than their women peers. In contrast, women graduate students, who do not embody masculinity, may feel more pressure to conform to the strict norms of competition that are associated with traditional masculinity.